Advanced Delivery of Poorly Water Soluble Drug Atorvastatin by Lipid Based Formulation - DESHMUKH, AMOL S.; MAHAJAN, VIJAY R. (Asian Journal of Pharmaceutical Research and Development, 2015)
Atorvastatin Calcium used to lower cholesterol level in plasma of body by competitive inhibiting HMG-CoA reductase, the rate determining enzyme in cholesterol biosynthesis via the mevalonate pathway. However its effectiveness is limited by its poor water solubility and very low oral bioavailability. Therefore the aim of present investigation was to develop an optimal lipid based formulation for advanced delivery of poorly water soluble drug Atorvastatin Calcium, for enhancing its aqueous solubility and oral bioavailability. Oil and surfactants were screened based on drug solubility. Pseudo-ternary phase diagrams were constructed to determine suitable surfactant to cosurfactant ratio for the development of lipid based formulation as SMEDDS. Atorvastatin calcium loaded SMEDDS was developed and characterized. Solidification of SMEDDS was done by spray drying technique using aerosil 200 as solid carrier. The drug release study shows that the release of Atorvastatin will enhances in SMEDDS formulation as compared to plain drug.